Seasonal dynamics of phyllosphere epiphytic microbial communities of medicinal plants in farmland environment - He, Chao; Zhang, Man; Li, Xianen; He, Xueli (Frontiers in Plant Science, 2024)
The phyllosphere of plants is inhabited by various microorganisms, which play a crucial role in plant physiological metabolism.Currently, there is limited research on the dynamic effects of species and seasons on plant phyllosphere microbial community diversity and microbial interactions. In this study, high-throughput sequencing technology was used to sequence the leaf surface parasitic microorganisms of five medicinal plants (Bupleurum chinense, Atractylodes lancea, Salvia miltiorrhiza, Astragalus membranaceus, and Lonicera japonica). The results showed that bacteria and fungi clustered into 3,898 and 1,572 operational taxonomic units (OTUs), respectively. Compared to host species, seasons had a more significant impact on the α diversity of bacteria and fungi. The heterogeneity of phyllosphere microbial communities was greater in winter compared to summer. Key species analysis at the OTU level and Spearman correlation analysis demonstrated significant preferences in microbial interactions under plant and seasonal backgrounds. The network connections between bacterial and fungal communities significantly increased during seasonal transitions compared to connections with plants. This study enhances our understanding of the composition and ecological roles of plant-associated microbial communities in small-scale agricultural environments. Additionally, it provides valuable insights for assessing the biodiversity of medicinal plants.